Susceptibility of Lasioderma serricorne (F.) life stages exposed to elevated temperatures - Yu, Chun (Kansas State University, 2008)
Heat treatment of food-processing facilities involves using elevated temperatures (46 to 60°C for 24 h) for management of stored-product insects. Heat treatment is a viable alternative to the fumigant methyl bromide, which is phased out in the United States as of 2005 because of its adverse effects on the stratospheric ozone. However, very little is known about responses of the cigarette beetle, Lasioderma serricorne (F.), a pest associated with food-processing facilities, to elevated temperatures. The main objective of my research was to evaluate stage-specific susceptibility of L. serricorne to elevated temperatures to identify the most heat tolerant stage. In the laboratory, I found L. serricorne was able to develop on ground, pelleted feed at 28°C and 65% RH; however, there is no data on the biology of this species on this diet. Therefore, several life history parameters of L. serricorne were studied on ground, pelleted feed at 28°C and 65% RH, to facilitate harvesting stages of specific ages in large numbers for assays with elevated temperatures. The mean duration for eggs was 8.1 d, and the mean egg survivorship was 92.0%. There were four discrete instars, and the mean durations of first, second, third, and fourth instars were 4.7, 4.5, 4.7, 11.8 d, respectively. The survivorship of first through third instars was about 99%, whereas that of fourth instars was 85%. The mean pupal duration was 4.6 d, and pupal survivorship was 98%. Newly eclosed unmated female adults lived 5 d longer than unmated males (29 d), whereas, mated males lived 6 d longer than mated females (17 d). Mated females started laying eggs on the third day after emergence and continued this activity for an additional six to eight days. Females, on average, laid 105 eggs with a mean daily output of 12 eggs. The data reported here provide new information on the biology of L. serricorne on ground, pelleted feed, which appears to be an optimal diet for mass rearing this species. Exposure of eggs, young larvae (3 to 4- July 2007 did not clearly show which of the life stages was heat- tolerant. However, exposure of all life stages to fixed times at 46, 50 and 54°C and 25% RH in the laboratory indicated eggs to be the most heat-tolerant stage. Time-mortality responses, at each of these three d old), old larvae (20 to 21-d old), and adults during heat treatment of a food-processing facility in 20-22 temperatures, showed that the time for 99% mortality (LT99) based on egg hatchability and egg-to-adult emergence was not significantly different at each temperature. The LT99 based on egg hatchability at 46°C was 605 min and it decreased to 190 min at 50°C and 39 min at 54°C. Therefore, during structural heat treatments eggs should be used in bioassays for gauging heat treatment effectiveness, because treatments aimed at controlling the egg stage should control all other life stages of L. serricorne.
Keywords: Cigarette beetle; Heat treatment; Agriculture, Food Science and Technology (0359)